2016
DOI: 10.3390/proteomes4040041
|View full text |Cite
|
Sign up to set email alerts
|

Advances of Salivary Proteomics in Oral Squamous Cell Carcinoma (OSCC) Detection: An Update

Abstract: Oral cancer refers to malignancies that have higher morbidity and mortality rates due to the late stage diagnosis and no early detection of a reliable diagnostic marker, while oral squamous cell carcinoma (OSCC) is amongst the world’s top ten most common cancers. Diagnosis of cancer requires highly sensitive and specific diagnostic tools which can support untraceable hidden sites of OSCC, yet to be unleashed, for which plenty of biomarkers are identified; the most recommended biomarker detection medium for OSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 48 publications
0
42
0
Order By: Relevance
“…The alpha‐1‐acid glycoprotein, alpha‐1B glycoprotein, alpha‐amylase, beta‐2‐glycoprotein, carbonic anhydrase 1, cystatin‐SA, hemopexin, phosphoglycerate kinase, and serum albumin were identified as potential salivary markers of OSCC .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alpha‐1‐acid glycoprotein, alpha‐1B glycoprotein, alpha‐amylase, beta‐2‐glycoprotein, carbonic anhydrase 1, cystatin‐SA, hemopexin, phosphoglycerate kinase, and serum albumin were identified as potential salivary markers of OSCC .…”
Section: Resultsmentioning
confidence: 99%
“…A potential way of improving our diagnostic tools is to perform in‐depth salivary analyses to discover and to assess biochemical and immunological markers in the saliva for early oral cancer diagnosis . Biomarkers identified in the last decades in biological fluids can be linked to carcinogenesis and may serve as prognostic factors and saliva is a new clinical biomarker source that can be easily collected by noninvasive means . As there is direct contact between saliva and the oral lesion(s), disease‐related concentration changes of saliva ingredients may provide as good or better clues than serum samples .…”
mentioning
confidence: 99%
“…Salivary screening is currently the best choice as the primary screening test for highrisk cases of OSCC because the collection procedure is noninvasive and low cost [21,22]. Several studies have demonstrated the feasibility of using salivay miRNAs and long noncoding RNAs (lncRNAs) as potential biomarkers of OSCC [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The human saliva revolution in medical and dental sciences through its property as a "mirror of body health" in the last decade brought many disease detections through its compositional changes in disease conditions [5]. Human oral cavity consists of different sources, such as salivary glands (major and minor), gingival crevicular fluid (GCF), microbes, and oral epithelial sheds for the production of whole mouth fluid (WMF) [6][7][8][9][10][11][12]. This fluid is 99% water, but 1% consists of DNA, mRNA, microRNA, proteins, metabolites, and microbiota which are utilised as a diagnostic fluid for disease analysis and even for forensic analysis [13,14].…”
Section: Paradigm Shift From Central Laboratory (Cl) To Point-of-carementioning
confidence: 99%